Controls on the scales of equilibrium during granulite facies metamorphism. (22nd January 2021) - Mitchell, Ruairidh J.; Johnson, Tim E.; Evans, Katy; Gupta, Saibal; Clark, Chris
Abstract: Phase equilibrium modelling is commonly employed to constrain the pressure–temperature ( P–T ) evolution of granulite facies rocks, from which their geodynamic setting may be inferred. However, defining a suitable equilibrium volume in such rocks is non‐trivial due to heterogeneities in protolith composition and open system behaviour, including melt loss or gain and deformation. Consequently, equilibrium volumes and the mineral assemblages they contain may vary both temporally and spatially within a single rock. Additionally, despite the extreme temperatures they attained, granulites commonly contain microtextures indicating gradients in chemical potential after the metamorphic peak. This study assesses the processes that control compositional heterogeneity between equilibrium volumes in a suprasolidus granulite and the consequences for the development of a range of microstructures. An approach combining phase equilibrium forward modelling and chemical potential diagrams is used to simulate the suprasolidus evolution of two adjacent equilibrium volumes in an Mg‐rich metapelite. Assuming equilibrium within the two compositional domains, evolving granulite facies assemblages vary along a high T/P (125°C/kbar) clockwise P–T path representative of high T/P metamorphic terranes. Many retrograde microtextures in metapelitic rocks can be reproduced by considering chemical potential (µ) gradients in µMgO, µFeO and µCaO between phases, assuming (a) the presence of melt on grain boundaries, (b) that Al2 O3 is perfectly immobile and (c) that K2 O and Na2 O are perfectly mobile. Additionally, documented microtextures in granulites imply local SiO2 ‐undersaturation, despite the presence of matrix quartz in the rock. Preserving such chemical potential gradients requires that solid phases are chemically and physically isolated from melt. Efficient prograde melt drainage may lead to a loss in melt interconnectivity at high temperature (>900°C), meaning that equilibration of centimetre‐scale compositional domains is controlled by solid‐state diffusion. The presence of isolated pockets of viscous melt allows the formation of discontinuous intergranular reaction microtextures.